The arrival of the smartest: In favour of a pluralistic account of the evolution of cognition - Airoldi, Giorgio (Aufklärung: journal of philosophy, 2021)
The great advances of the last decades both in cognitive theories and in evolutionary biology have not yet fully merged. Most evolutionary hypotheses around the mind still rely on classical cognitivism, while most theories of cognition still look for adaptive explanations. We believe that the merging of novel cognitive theories into a pluralistic account can greatly improve our understanding of both what cognition is and how it evolved.